Indoor Environment in Kindergartens Located in the North of Portugal: Evaluation of Thermal Comfort and Carbon Dioxide Concentration - Eva Barreira; Ricardo M. S. F. Almeida; Joana Guimarães (Buildings)
Adequate school buildings are essential for the development of children, young people, and adolescents, as they must provide conditions that support their well-being and health. A healthy and comfortable indoor environment is critical for students’ performance in the learning process. This study aims to evaluate the indoor environment in kindergartens located in northern Portugal, with a primary focus on thermal comfort and indoor air quality. To achieve this, five buildings with varying construction characteristics were monitored, with temperature and relative humidity measurements taken in classrooms of different orientations over time. Additionally, the outdoor climate was also monitored. Based on the collected data, thermal comfort was evaluated using the adaptive model defined by the European standard EN 16798. Continuous monitoring of carbon dioxide concentration was also conducted in three of these buildings. The results reveal significant heterogeneity among the buildings, demonstrating the influence of construction characteristics on the interior thermal conditions. The recorded temperatures ranged from 10 °C to 27 °C, highlighting a substantial variability in performance across the different buildings. Particularly, the orientation and size of glazed openings, together with the lack of thermal insulation in the building envelope, especially in the roof, were found to have an important impact on the thermal comfort of the occupants. Furthermore, a relationship was observed between the daily maximum carbon dioxide concentration and the outdoor temperature, as a result of users’ efforts to minimize uncontrolled air infiltration, by limiting the opening of doors and windows, with consequences in the air exchange between the interior and exterior.